The Concept of Kufr in Social Behavior According to the Qur'an - Faiqotul Faiqotul Himmah; Achmad Khudori Soleh (Universitas Islam Cordoba Banyuwangi, 2026)
Kufr is a condition in which a person does not follow the provisions of the Shari'a that have been outlined by Allah, and often denies the provisions of the Shari'a of Allah. Kufr is a matter that is discussed a lot in the Qur'an, including in social behavior. The purpose of this research is to find out the concept of kufr in social behavior according to the Qur'an. The method used in this study is a literary qualitative method, and the analysis used is maudhu'i analysis, the object of this study is the concept of Kufr which is associated with social behavior. The results of the study 1) kufr in the Qur'an in all its forms of words is repeated 531 times. 2) There are two kinds of factors that cause Kufr, namely internal and external. 3) The Qur'an explains Kufr not only about disbelief or disbelief against faith, but kufr in social behavior that occurs in our social life which without us realizing it, often intersects including breaking rules, people breaking promises, insulting or bullying others, lie and lie, and intimidate others.